Comparison of rebozo technique and warm compress on reducing pain intensity in pregnant women during the active phase i in the working area of Wanayasa Health Center, Purwakarta Regency, 2025 - Rosyeni, Yeni (Science Midwifery, 2025)
Labor pain can lead to decreased contractions and prolonged labor. According to World data in the World Health Organization in 2019, the case of mothers with painful labor states that only 10-15% of labor lasts without pain, thus the data is most found in mothers with painful labor, namely a prevalence of 85-90% of labor takes place with pain. The rebozo technique and warm compress are new non-pharmacological therapies to reduce the intensity of labor pain that are easy, inexpensive, and comfortable for mothers. Objective: To find out the comparison of rebozo technique and warm compress on the intensity of pain reduction in pregnant women during the first active phase. Research Method: The type of research is Quasi experiment pre-test and post-test two group design. Technique of sampling purposive samples. The data were analyzed by paired T test and Wilcoxon test. Results: The results of the analysis showed that the average respondent after being given the rebozo technique experienced a decrease in pain of 3.27, while the respondents after being given warm compresses experienced a decrease in pain of 4.87 with a p-value of 0.006 so it was concluded that there was a significant difference in the reduction in the intensity of labor pain given by the rebozo technique and warm compress, where the rebozo technique was more effective compared to the administration of warm compresses. Suggestion: Apply the natural method of the rebozo technique during the delivery process as one of the mother's loving care that will provide a sense of comfort and can reduce labor pain in childbirth mothers.